2010
DOI: 10.1364/oe.18.003264
|View full text |Cite
|
Sign up to set email alerts
|

Imaging gold nanoparticles in living cell environments using heterodyne digital holographic microscopy

Abstract: This paper describes an imaging microscopic technique based on heterodyne digital holography where subwavelengthsized gold colloids can be imaged in cell environment. Surface cellular receptors of 3T3 mouse fibroblasts are labeled with 40 nm gold nanoparticles, and the biological specimen is imaged in a total internal reflection configuration with holographic microscopy. Due to a higher scattering efficiency of the gold nanoparticles versus that of cellular structures, accurate localization of a gold marker is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 27 publications
(28 reference statements)
3
44
0
Order By: Relevance
“…All the driving signals are synchronized by a common 10 MHz clock. Figure 2 illustrates our reconstruction procedure [4,5] with non-Doppler shifted images. We have considered here four phase holograms: H = (I 0 − I 2 ) + j(I 1 − I 3 ) (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…All the driving signals are synchronized by a common 10 MHz clock. Figure 2 illustrates our reconstruction procedure [4,5] with non-Doppler shifted images. We have considered here four phase holograms: H = (I 0 − I 2 ) + j(I 1 − I 3 ) (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The reconstruction procedure is similar to the one used in previous works [50,51]. To illustrate reconstruction, let us consider 4 phase detection of the ballistic peak signal (no Doppler shift).…”
Section: Spatial Filtering and Reconstructionmentioning
confidence: 99%
“…This latter study identified that this approach would trail single particle photothermal interferometry by an order of magnitude or greater in SNR and that the need for a widely distributed reference field might cause sample damage when imaging cells. This limitation was explored further by this group [48], where they imaged nanoparticles in the presence of cells using a similar scheme. The interface of the cell with the evanescent field showed the cell structure in contact with the prism.…”
Section: Digital Holographymentioning
confidence: 99%